Control interno contable en los costos de producción y su aporte a la razonabilidad de los estados financieros - Jumbo Romero, Andrea Alejandra (2015)
This paper uses the internal control to recognize the gaps in the company ABEDAYOR SA, reaching for designing policies to control production costs in the company through procedures. The main activity of the company is the production and sale of bananas and seeks to reduce production costs and improve the fairness of the financial statements, to help control the processes running for operation. The research focuses on the diagnosis of the company, analyzing processes that apply to run their production costs; where it was shown that the processes of production costs were not related to earnings, for it intends to implement internal control policies on the three elements of production costs such as direct material, direct labor and other costs manufacturing and so have control of the most important processes. In implementing the policy proposals analyzed this research focuses positively on the social dimension, as well as technical; aimed at implementing processes that will improve the economic situation of the company and the job security of current employees of the company and the possible creation of new jobs. As for the economic dimension, investment of this proposal is appropriate because the controls that will be implemented will control production costs. This research was based on a field study combined with an analysis of the economic situation in the years 2013 and 2104; projected to improve this year.